2006
DOI: 10.1055/s-2006-926591
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Interscalene Brachial Plexus Anaesthesia: Differences in Success between Patients of Normal and Excessive Weight

Abstract: Portable ultrasound provides efficient depiction of the interscalene plexus structures in obese patients and, when used for guidance of regional blockade, renders similar results as in patients of normal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 14 publications
0
21
2
3
Order By: Relevance
“…110 Schwemmer et al studied ultrasound-guided ISB in 70 patients who were a mix of obese and normal weight individuals. 108 A high-frequency probe was used, and the authors found that nerve visualization in the obese group took 5 (1) min vs 4 (2) min in the normal weight group, unlikely to be clinically significant. There was no statistically significant difference in block success at 94% in the normal weight group and 77% in the obese group, most likely because of the small numbers involved.…”
Section: Regional Anesthesia In the Obese Patientmentioning
confidence: 99%
“…110 Schwemmer et al studied ultrasound-guided ISB in 70 patients who were a mix of obese and normal weight individuals. 108 A high-frequency probe was used, and the authors found that nerve visualization in the obese group took 5 (1) min vs 4 (2) min in the normal weight group, unlikely to be clinically significant. There was no statistically significant difference in block success at 94% in the normal weight group and 77% in the obese group, most likely because of the small numbers involved.…”
Section: Regional Anesthesia In the Obese Patientmentioning
confidence: 99%
“…Die Erfolgsrate für periphere Nervenblockaden ist bei hochgradiger Adipositas im Vergleich zu Normalgewichtigen geringer. Die Versagerquote kann jedoch durch ultraschallgestützte Punktion deutlich vermindert werden [22].…”
Section: Regionalanästhesieunclassified
“…Today, although success has increased with the use of ultrasonography in this field and complication rates have been decreased, the success rate is still not 100% and the possibility of serious complications has not been completely prevented. 7 In this study, a comparison the analgesia effects of the application of ultrasound-guided interscalene brachial plexus block consisting of bupivacaine and intra-articular bupivacaine in the postoperative period will be performed.…”
Section: Introductionmentioning
confidence: 99%